Experimental Study on Joining by Forming of HCT590X+Z and EN-AW 6014 Sheets Using Cold Extruded Pin Structures - Römisch, David; Kraus, Martin; Merklein, Marion (Journal of Manufacturing and Materials Processing, 2021)
Due to stricter emission targets in the mobility sector and the resulting trend towards lightweight construction in order to reduce weight and consequently emissions, multi-material systems that allow a material to be placed in the right quantity and in the right place are becoming increasingly important. One major challenge that is holding back the rapid and widespread use of multi-material systems is the lack of adequate joining processes that are suitable for joining dissimilar materials. Joining processes without auxiliary elements have the advantage of a reduced assembly effort and no additional added weight. Conventional joining processes without auxiliary elements, such as welding, clinching, or the use of adhesives, reach their limits due to different mechanical properties and chemical incompatibilities. A process with potential in the field of joining dissimilar materials is joining without an auxiliary element using pin structures. However, current pin manufacturing processes are mostly time-consuming or can only be integrated barely into existing industrial manufacturing processes due to their specific properties. For this reason, the present work investigates the production of single- and multi-pin structures from high-strength dual-phase steel HCT590X + Z (DP600, t(0) = 1.5 mm) by cold extrusion directly out of the sheet metal. These structures are subsequently joined with an aluminium sheet (EN AW-6014-T4, t(0) = 1.5 mm) by direct pin pressing. For a quantitative evaluation of the joint quality, tensile shear tests are carried out and the influence of different pin heights, pin number, and pin arrangements, as well as different joining strategies on the joint strength is experimentally evaluated. It is proven that a single pin structure with a diameter of 1.5 mm and an average height of 1.86 mm achieves a maximum tensile shear force of 1025 N. The results reveal that the formation of a form-fit during direct pin pressing is essential for the joint strength. By increasing the number of pins, a linear increase in force could be demonstrated, which is independent of the arrangement of the pin structures.
CRIS-Team WoS Importer:2021-04-30